Implementation Of Integrated Quality Management In The Islamic Education System - Nurzannah Nurzannah; Nurman Ginting; Hasrian Rudi Setiawan (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this paper/paper is to present pragmatically the implementation of integrated quality management (MMT), also known as Total Quality Management (TQM) in the Islamic education system. The presentation of this paper is supported by various research-related results and critical analysis of the management system of Islamic Education which is generally implemented in Indonesia. With the hope that Islamic education institutions can better manage education that is implemented, it can provide satisfying services, quality processes, involving all elements of education in total, namely; not only strive for the involvement of managers (principals) and employees (teachers and employees) but involve all elements of the school/madrasah including students and parents and the community, in achieving predetermined educational goals, while still evaluating to see the measurement of success education program implemented. Also to satisfy internal and external customers, and realize quality output.